The evolution of the crustal stress state of the Catoca kimberlite pipe area (northeastern Angola) - O. V. Lunina; A. S. Gladkov; D. P. Gladkochub; F. João; M. A. Karpenko; J. T. Félix; D. A. Koshkarev; E. V. Sklyarov (Геодинамика и тектонофизика)
This paper presents the first results of the geostructural and tectonophysical studies of the crustal stress state in the Catoca kimberlite pipe area at the southwestern flank of the Kasai Shield in the northeasternAngola. In the evolution of the crustal stress state, six main stages are distinguished by analyzing the displacements of markers, fold hinges, long axes of boudins, granite dikes of various intrusion phases and kimberlites, as well as fractures with striations. For each of these stages, a dominating horizontal tectonic stress and its orientation is identified. During stage 1 (NW extension and shearing) and at the beginning of stage 2 (NW compression), structures formed in the host rocks in brittle-plastic conditions. The replacement of plastic deformation by faulting could occur about 530–510 Ma ago, when the continental crust ofAfricahad completely formed. Stage 3 (radial, mainly NW extension) and stage 4 (shearing, NW extension, and NE compression) were the most important for kimberlite occurrence: in the Early Cretaceous, radial extension was replaced by shearing. Both stages are related to opening of the central segment of theSouth Atlantic. The main kimberlite magmas occurred during the break-up of the Angola-Brazilian segment of Gondwana. In the course of all the four stages, stress was mainly released by the NE- and E-NE-striking faults and, to a lesser extent, by the NW-striking and latitudinal faults. The initial stage of kimberlite magmatism is associated with the NE- and E-NE-striking faults due to the presence of the Precambrian zones of flow and schistosity, which facilitated the NW-trending subhorizontal extension. Stage 5 (NE compression) began in the second half of the Cretaceous and possibly lasted until the end of the Paleogene, and compression occurred mainly along the NW-striking faults. Regionally, it corresponds to two stages of inversion movements in the southern regions of Africa, during which theAngoladome-shaped uplift emerged and the shoulders of the East African rifts began to take shape. Stage 6 (horizontal extension, mainly in the N-NE direction) is related to the processes that took place in the southern segment of theTanganyikarift and the eastern coast of theAtlantic. Based on the results of our studies, it became for the first time possible to get an idea of the main stages in the evolution of the studied region. Further geostructural measurements and dating of the host rocks will provide for a more precise definition of the proposed stages.